2014
DOI: 10.6018/analesps.30.3.201201
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Learning and Academic Achievement: Why Does Groupwork Work?. [Aprendizaje cooperativo y rendimiento académico: ¿por qué funciona el trabajo en grupo?]

Abstract: Título: Aprendizaje Cooperativo y rendimiento académico: ¿Por qué funciona el trabajo grupal? Resumen: El aprendizaje cooperativo hace referencia a los métodos de enseñanza en los que los estudiantes trabajan en pequeños grupos para ayudarse a aprender. En este artículo se revisan cuatro de las principales perspectivas teóricas sobre los efectos del aprendizaje cooperativo en el rendimiento: motivacional, cohesión social, evolutiva y elaboración cognitiva. La evidencia de la investigación práctica en el aula a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
104
0
25

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(133 citation statements)
references
References 35 publications
4
104
0
25
Order By: Relevance
“…We must clarify that these 4 perspectives are not exclusive. On the contrary, they complement each other (Slavin, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…We must clarify that these 4 perspectives are not exclusive. On the contrary, they complement each other (Slavin, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…There exits many definitions on cooperative learning, but it could be briefly defined as small groups where students work together to maximize their own and others' learning through common goals, depending on each other to achieve them (Johnson, Johnson & Holubec, 2013;Sharan, 2014). Several research works have showed the benefits of this framework to achieve different positive outcomes: performance, motivation and social skills (Gillies, 2014;Kyndt et al 2013;Slavin, 2014), in subjects as different as Maths (Pons, Prieto, Lomeli, Bermejo & Bulut, 2014), science (Howe, 2013), or physical education (Fernandez-Rio, Sanz, Fernandez-Cando & Santos, 2017). Based on these findings, cooperative learning is considered a methodological tool that can help solve XXI st century students' needs (Johnson & Johnson, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it attempts to help solve the conundrum of why collaborative learning in general, and computer-supported collaborative learning (CSCL) specifically, sometimes works while at other times fails. At best, one can say that its purported benefits are not always consistent (Kester and Paas 2005;Kirschner et al 2009a;Slavin 2014). This variation could be because research has paid little attention to the human cognitive architecture that underlies group processes, the prior group experience, and the information distribution among collaborators.…”
mentioning
confidence: 99%
“…All the four important things should be a mutually reinforcing cohesion when learning takes place. In the first aspect, in view of Slavin (2014), motivationalist found a group bonding will help achieve the group's performance and ultimately success will be the success of the group together and motivate learners to be more persistent again in optimizing their performance in the group. Thus the motivation is always important affiliated with a joint work in study groups.…”
Section: Introductionmentioning
confidence: 99%